Housing Shortage in Libya: Solutions and Reasons for Failure During the Period 1970-2010 - Al sheibani, Gamal; Eaton, David (Dirasat in Economics and Business, 2013)
Housing shortages appeared in Libya in the early 1980s after a great boom during the 1970s. The authorities in Libya attempted to solve the housing shortage by undertaking to build 60000 publicly funded housing units in a three-year plan between 1995 and 1997. Unfortunately, this was not achieved due to several reasons. This paper discusses the Libyan authorities' approach in this matter, and the possible causes of its failure. The methodology followed is qualitative, comprising a survey of official documents and analysis of semi-structured interviews with responsible officers in the housing sector in Libya. The causes of the problems are presented, ones possible solution drawn. This paper is trying to spotlight on Libyan authorities' attempts to solve those issues and the reasons behind its failure.